PROPUESTA PARA LA CREACION EN EL CANTON BABAHOYO, DE UN BANCO GERMOPLASMA DE PLANTAS MEDICINALES NATIVAS, EN PELIGRO DE EXTINCION, QUE CONTRIBUYA A SU RECUPERACION Y PROPAGACION. - WILLIAN ADOLFO FILIAN HURTADO (2010)
PROPOSAL FOR THE CREATION IN THE CANTON BABAHOYO, OF A GERMOPLASM BANK OF NATIVE MEDICINAL PLANTS, IN DANGER OF EXTINCTION, WHICH CONTRIBUTES TO THEIR RECOVERY AND PROPAGATION.